EXPLORING STUDENTS’ ATTITUDE TOWARDS ENGLISH ONLINE LEARNING USING MOODLE DURING COVID-19 PANDEMIC AT SMK YADIKA BANDARLAMPUNG - Robekka Risten Fransiska Sinaga; Reza Pustika (Journal of English Language Teaching and Learning, 2021)
The ministry of education in Indonesia had declared the spread out of Covid-19 pandemic.  To overcome this current situation, Learning from Home (LFH) is implemented for all subjects in the educational institution. LFH is conducted to all courses, including English class, through an online learning platform, one of which is Moodle. Moodle can cover up teaching and learning English courses during the spread out of Covid-19. Theoretically, the researcher organized the framework by examining students’ attitudes and analyzing how students overcome difficulties in learning English during online learning through Moodle. The researcher used self-analysis and student opinions to determine the degree of consensus based on how students felt or acted in response to the current situation. While, the favorable or unfavorable (positive or negative) of students’ attitude can be changed due to the characteristics of students’ thoughts (cognitive), feeling (affective), and behavioral (conative). However, to reduce the students’ negative attitude is to change the focus of students and the students’ acceptance. In this research, the researcher used qualitative research that focused on word descriptively. The questionnaire was given to 30 students and 6 students participated in an interview session. The questionnaire statements and questions of interview were adapted from the research of Brown (1994) about components of students’ attitude. The result of this research shows a positive attitude to implement Moodle as a learning platform. They have also demonstrated a positive attitude toward the importance of learning English in vocational high school. However, the students also find some self-problem in learning English during the implementation of Learning from Home (LFH), where students sometimes lack self-management to follow the learning activities.